Characterization and Soil-Site Suitability Evaluation for Different Crops in Sarupathar Block of Golaghat District, Assam - Samiron Dutta (Journal of the Indian Society of Soil Science, 2022)
The present study was conducted in Sarupathar block of Golaghat district of Assam in order to characterizeand evaluate the soils for their suitability for some important crops. Six representative soil profiles werecollected covering the entire block area and soil-site characteristics were studied in detail. The soils weredark grayish brown (10YR 4/2) to very pale brown (10YR 7/3) in colour, sandy loam to clayey in texturewith subangular blocky structure. Sand, silt and clay contents of the soils ranged from 14.4-35.6, 32.5-58.6and 18.8-41.2%, respectively. The bulk density and particle density of the soils ranged from 1.14-1.38 and2.10-2.39 Mg m-3, respectively. Organic carbon content of the soil varied from low to high (1.2-12.6 g kg-1).The cation exchange capacity of the soils was low [7.2-11.9 cmol(p+) kg-1] and base saturation ranged from24.2-47.7%. Soils were classified as Oxyaquic Dystrudepts (P1, P2 and P3), Typic Dystrudepts (P4 and P5)and Aquic Dystrudepts (P6) at the subgroup level. The soils were rated as good except the soils of P4which were rated as excellent as per the storie index rating. The soil-site suitability was evaluated for 17crops (maize, pigeon pea, sunflower, sesame, potato, chilli, tea, arecanut, citrus, banana, lemon grass,pepper, vanilla, ginger, turmeric, cardamom and oil palm) following the simple limitation approach. Majorityof the soils were found to be marginally suitable for the crops under the present condition. Some soilsshowed moderate suitability for crops like pigeon pea, tea, citrus, banana and oil palm. The soils can beimproved to moderately suitable and in few cases to highly suitable class with specific interventions.